Biaproksymacja wirowych zjawisk ekonomicznych - Juzwiszyn, Jacek (Biapproximation of rotational economic phenomena, 2007)
Rotational-spiral trajectories appear in the three-dimensional space, in which are observed vectors of the volume, price and time components. The trajectories define cones’ side superficies in certain time intervals. The cones cut ortogonally and projected onto a plane, which is extended on volume and price axes, will construct families of rotating circles (ellipses). In the article there is considered the idea of double approximation of the family of rotating circles.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1189, s. 183-194